Pengaruh Pandemi Covid-19 Terhadap Kunjungan ANC Ibu Hamil di Puskesmas Tanasitolo Kabupaten Wajo - Yenni Yenni; Andi Tenri Angka (JURNAL KEPERAWATAN SISTHANA, 2020)
Antenatal care or pregnancy examination is a service provided to pregnant women by carrying out pregnancy examinations and supervision to optimize the mental and physical health of pregnant women so that they are able to face childbirth, postpartum, preparation for giving breast milk (ASI) and the return of normal reproductive health. In this COVID-19 pandemic situation, there are many restrictions on almost all routine services including maternal and neonatal health services. For example, pregnant women are reluctant to go to community health centers or other health service facilities because they are afraid of being infected. The aim of the research is to determine the influence of the Covid-19 Pandemic on Pregnant Women's Anc Visits at the Tanasitolo Community Health Center, Wajo Regency. The type of research used is a cross sectional study. The sample was 80 pregnant women who visited ANC at the Tanasitolo Community Health Center, Wajos Regency, where random sampling was used as a sampling technique. The results of the research show that based on the chi square statistical results, a p value = 0.000 < ? = 0.05 is obtained, which indicates that there is an influence of the Covid-19 pandemic on ANC visits of pregnant women at the Tanasitolo Community Health Center, Wajo Regency. The conclusion is that there is an influence of the Covid-19 pandemic on ANC visit of pregnant women at the Tanasitolo Community Health Center, Wajo Regency.